Pembingkaian Berita Motif Kasus Pembunuhan Keluarga di Magelang pada Portal Berita Republika.co.id dan Tribunnews.com (Analisis Framing Robert N. Entman) - Nurhasanah Nurhasanah; Hendra Setiawan (Peneliti.net, 2023)
On November 28, 2022, the community was shocked by the case of a family murder in Magelang. The murder victims were three people in one family, the perpetrators turned out to be members of his own family. The three victims consisted of father, Abbas Ashar (58), Mother Heri Iryani (54), and Dhea Chairunnisa (24). The perpetrator was the second child of the family, the perpetrator killed by poisoning his family. The motive of the perpetrator is still being investigated. The author conducted a framing analysis of two news articles containing the suspect's motive for committing the murder through Robert N. Entman's framing analysis. The two articles came from the Republika.co.id news portal with the news title